Secular Inflation by Friedrich-Karl Lage. D. Reidel Publishing Company, Dordrecht, Holland, 1961. (The Pakistan Development Review, 1970)
The main theme of the book under review is an inquiry into the nature and canses of secular inflation. In defining the term 'secular', the author has followed Simon Kuznets who defined it as an irreversible, continuous movement over a period 'greater than the average duration' of an economic cycle. 'Secular inflation', hence, may include every type of inflation as long as it extends over a secular period and in effect results into an irreversible money depreciation. As a measure and symptom of secular inflation, Lage, like many others, suggests price levels and cost-of-living indices. But due to the lack of accurate figures, a search for a direct proof of the existence and the scope of secular inflation is not always successful.